Study on Influence of Cavity and Water Mist on Flame Propagation of Gas Explosion in a Pipeline - Shicheng Gu; Shujie Yuan; Zhuo Yan; Xiaoxue Xu (Geofluids)
For studying the influence of the cavity and water mist on the flame propagation of gas explosion, a rectangular steel cavity of size of length 80 cm×width 50 cm×height 20 cm was designed. The influence of the cavity and it with water mist on explosion flame propagation in a large circular gas explosion system with a length of 34 m was studied. The change of gas explosion flame in the pipeline was analyzed. The results showed that the intensity and flame propagation velocity increase after the explosion flame passes through the straight pipeline, and the attenuation rates are 4.93% and -2.48%, respectively. After the explosion flame passes through a rectangular cavity of length 80 cm×width 50 cm×height 20 cm, its intensity and propagation speed are inhibited, and the attenuation rates are 66.58% and 45.26%, respectively. After the explosion flame passes through the rectangular cavity of the size of length 80 cm×width 50 cm×height 20 cm with water mist, the intensity and propagation speed are inhibited much more, and the attenuation rates are 85.09% and 65.85%, respectively. The influence of the cavity with water mist on flame attenuation of gas explosion is better than that of the cavity alone. Based on theoretical analysis, it is concluded that the inhibition influence of the cavity on explosion flame propagation is mainly due to repeated reflection of flame in the cavity, which results in the attenuation of its energy. The inhibition influence of water mist is mainly due to its heat absorption by vaporization.